Identifying The Purchasing Power Parity of Indonesia Rupiah (IDR) based on BIG MAC Index - Tongam Sihol Nababan (Muhammadiyah University Press, 2016)
The aim of this study is to identify : (1) profile of exchange rate and purchasing power parity of IDR against US based on Big Mac Index compared to the exchange rate of other countries, and (2) the position of the Big Mac Affordability of Indonesia compared to other ASEAN countries. The results showed that based on Big Mac index during the period April 1998 up to January 2015, IDR exchange rate tends to be undervalued against the USA dollar. The cause of the currency tends to be in a position of undervalued due to the components of non-tradable have not been included in Big Mac index. The index of Big Mac Affordability indicates that there is a great disparity of income between Singapore and five other ASEAN countries. The purchasing power of the real income of the people in Singapore is nearly five times the real income of the people in Indonesia.